Improved early postoperative cognition in elderly gastrointestinal patients: a randomized controlled trial on the role of ultrasound-guided stellate ganglion block - Xue, Ruyue; Li, Yuexian; Zhan, Mei; Yang, Lin; Sun, Defeng (Frontiers in Aging Neuroscience, 2025)
BackgroundThis study evaluates the impact of ultrasound-guided stellate ganglion block (SGB) on early postoperative cognitive dysfunction (POCD) in elderly patients who underwent laparoscopic gastrointestinal (GI) surgery, as well as its potential effect on oxidative stress and inflammatory responses.MethodsIn this randomized controlled trial, 104 elderly patients scheduled for elective laparoscopic GI surgery were randomized to receive ultrasound-guided SGB before general anesthesia (SGB group) or general anesthesia alone (control group). A total of 98 patients completed the study. Cognitive function was assessed using the Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) preoperatively, and on postoperative days one and three. The perioperative recordings included mean arterial pressure, heart rate, and the bispectral index. Blood samples were analyzed for interleukin-6 (IL-6), superoxide dismutase (SOD), and malondialdehyde (MDA).ResultsThe SGB group had a significantly lower incidence of POCD on postoperative day one (p < 0.05). IL-6 and MDA levels were significantly lower, while SOD levels were higher in the SGB group, when compared to the control group (p < 0.05). MDA levels were notably lower on postoperative day three in the SGB group (p < 0.05). Both groups showed significant changes in IL-6, SOD and MDA levels, when compared to preoperative values. The hemodynamic indicators showed a slight reduction in intraoperative blood pressure and decreased numerical rating scale scores on the first postoperative day without significant differences in other indicators.ConclusionPreoperative SGB reduces early POCD in elderly patients who undergo laparoscopic GI surgery, possibly through the inhibition of oxidative stress and inflammatory responses.